SPECIES COMPOSITION OF THE CULICOIDES FAUNA IN THE REPUBLIC OF MACEDONIA - Cvetkovikj, Aleksandar; Cvetkovikj, Iskra; Rashikj, Ljubica; Angjelovski, Branko; Stefanovska, Jovana (Faculty of veterinary medicine in Skopje, 2018)
Culicoides spp. are small nematocerous biological vectors of pathogens of veterinary and medical importance, including the viruses of bluetongue, African horse sickness and epizootic hemorrhagic disease. The genus Culicoides consists of more than 1400 species, out of which about 30 have been implicated as a vector of viruses and other pathogens. In the Republic of Macedonia there were two major bluetongue outbreaks (in 2001 and 2014) and the culicoides involved in the transmission of this disease were never investigated. Hence, the Culicoides monitoring to determine the potential vectors, species diversity and abundance in Macedonia was started in 2016. This text provides a checklist of the Culicoides spp. from Macedonia collected during 2016 and 2017. Using suction light traps the collections were performed on seven cattle dairy farms. The sampling was carried out twice per month for two consecutive nights (May-October) and once per month for one night (November-April). The collected Culicoides were identifi ed according to the previously described wing patterns of the females and the genital morphology of the males. A group of females morphologically identifi ed as Culicoides obsoletus/Culicoides scoticus were identifi ed to separate species level by conventional PCR. Overall, 264 collections were performed and a total of 140,663 Culicoides were identifi ed. The identifi ed Culicoides belonged to 15 species/groups: Culicoides obsoletus s.l./Culicoides scoticus, Culicoides imicola, Culicoides pulicaris, Culicoides punctatus, Culicoides newsteadi, Culicoides circumscriptus, Culicoides fl avipulicaris, Culicoides dewulfi , Culicoides bysta, Culicoides lupicaris, Culicoides paradoxalis, Culicoides fagineus/Culicoides impunctatus, Culicoides odibilis gp, Culicoides nubeculosus/riethi/puncticollis and Culicoides without wing pattern). Culicoides obsoletus s.l./Culicodies scoticus were the most abundant species with predominance of Culcioides obsoletus s.l. over Culicoides scoticus.
Keywords: Culicoides, vector species, Macedonia